Influence of Meteorological Conditions on Artificial Ice Reservoir (Icestupa) Evolution - Balasubramanian, Suryanarayanan; Hoelzle, Martin; Lehning, Michael; Bolibar, Jordi; Wangchuk, Sonam; Oerlemans, Johannes; Keller, Felix (Frontiers in Earth Science, 2022)
Since 2014, mountain communities in Ladakh, India have been constructing dozens of Artificial Ice Reservoirs (AIRs) by spraying water through fountain systems every winter. The meltwater from these structures is crucial to meet irrigation water demands during spring. However, there is a large variability associated with this water supply due to the local weather influences at the chosen location. This study compared the ice volume evolution of an AIR built in Ladakh, India with two others built in Guttannen, Switzerland using a surface energy balance model. Model input consisted of meteorological data in conjunction with fountain discharge rate (mass input of an AIR). Model calibration and validation were completed using ice volume and surface area measurements taken from several drone surveys. The model was successful in estimating the observed ice volume evolution with a root mean square error within 18% of the maximum ice volume for all the AIRs. The location in Ladakh had a maximum ice volume four times larger compared to the Guttannen site. However, the corresponding water losses for all the AIRs were more than three-quarters of the total fountain discharge due to high fountain wastewater. Drier and colder locations in relatively cloud-free regions are expected to produce long-lasting AIRs with higher maximum ice volumes. This is a promising result for dry mountain regions, where AIR technology could provide a relatively affordable and sustainable strategy to mitigate climate change induced water stress.